Uso de google classroom para mejorar los aprendizajes de inglés en estudiantes de segundo nivel de las carreras de idiomas extranjeros en la Universidad Nacional de la Amazonía Peruana Iquitos 2022 - Yalta Mera, Johana Patricia (2023)
The purpose of this research study was to assess the effectiveness of using Google Classroom in second level Foreign Language teacher-education students’ English performance at the National University of the Peruvian Amazon, Iquitos 2022. The research type was evaluative and field study, contemporary transectional, univariate, and quasi experimental designs, including a control group, pre-test, and post-test. The population and sample consisted of 45 students. Data collection involved tests of reading, listening, speaking, and writing. The results obtained of the post-test demonstrate the experimental group was higher than the control group in terms of mean scores (17,151>14,522). The same happened in each dimension: listening (18,167>14,706), speaking (15,866>14,292), reading comprehension (18,696>17,441), and writing (15,875>11,647). In summary, the difference is statistically significant in students’ English performance after using Google Classroom, as p-value = 0.000 < α = 0.05.